Hollow columnar structure tantalum oxide and preparation method thereof
By using fluorotantalic acid solution and alkaline ammonium salt solution in the production of tantalum oxide, a hollow columnar structure tantalum oxide was prepared, which solved the problems of uneven particles and single structure in the existing tantalum oxide production, and achieved the product Efficient, economical and environmentally friendly production.
Patent Information
- Application Number
- CN202411670830.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-21
AI Technical Summary
In the existing production process of tantalum oxide, there are problems of uneven particles, large particle size and single structure, and the preparation process of highly ordered mesoporous tantalum oxide is complex, costly and harmful to the environment and the human body.
The hollow columnar structure tantalum oxide is prepared by injecting the fluorotantalic acid solution into the alkaline ammonium salt solution for precipitation reaction, and the reaction conditions such as stirring speed, washing and calcining temperature are controlled.
The prepared hollow columnar structure tantalum oxide has good dispersion, fluidity and uniform particle size distribution, and has low production cost and little harm to the environment and human body. It has a simple method and high yield.
Smart Images

Figure CN119490228A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing tantalum oxide by hydrometallurgy, and in particular relates to tantalum oxide with a hollow columnar structure and a preparation method thereof. Background Art
[0002] Tantalum oxide is in high demand in the fields of ceramic materials and electronic materials, and is also used as a catalyst in the field of optoelectronics. The applications in the above fields all require tantalum oxide to have the characteristics of small particle size and high specific surface area. At present, tantalum oxide production is mostly large-particle agglomerate structure, with problems of uneven particles and large particle size, and the product needs to be crushed. At the same time, the current tantalum oxide structure is relatively simple, and it is mostly a solid structure under an electron microscope.
[0003] The related technology discloses the synthesis of highly ordered mesoporous tantalum oxide. The prepared mesoporous tantalum oxide has uniform and small particle size. However, the preparation process uses block copolymer surfactant P123 as a structure directing agent and performs shaping treatment through a sol-gel method to allow the tantalum oxide to grow in a specific structure. The production process is complicated, the production cycle is long, and the cost is high.
[0004] The related technology also discloses a method for manufacturing hollow microparticle-type tantalum oxide and / or niobium oxide, which prepares tantalum oxide / niobium with a hollow structure. However, the technical method is to add hydrazine or a hydrazine solution to a tantalum / niobium oxide solution. However, the use of hydrazine has a high production cost and is extremely harmful to the environment and human body. Summary of the invention
[0005] The purpose of the present invention is to provide a hollow columnar tantalum oxide and a preparation method thereof. The method provided by the present invention can prepare a hollow columnar tantalum oxide, and the hollow columnar tantalum oxide product has good dispersibility, good fluidity and uniform particle size distribution; at the same time, the preparation method has low cost and little harm to the environment and human body.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing tantalum oxide with a hollow columnar structure, comprising the following steps:
[0008] Injecting a fluorotantalate solution into a precipitant for precipitation reaction to obtain a reaction solution; the pH value of the reaction solution is ≥9, the mass concentration of the fluorotantalate solution is ≤100 g / L in terms of Ta2O5, and the precipitant is an alkaline ammonium salt solution;
[0009] Separating the reaction liquid into solid and liquid to obtain a solid phase product;
[0010] The solid phase product is washed, dried and calcined in sequence to obtain the hollow columnar tantalum oxide.
[0011] Preferably, the mass concentration of the fluorotantalate solution is 50 to 100 g / L in terms of Ta2O5; and the injection flow rate of the fluorotantalate solution is 500 to 2000 L / h.
[0012] Preferably, the precipitant is an ammonium carbonate solution, and the molar concentration of the ammonium carbonate solution is 0.5 to 1.5 mol / L.
[0013] Preferably, the precipitation reaction is carried out under stirring conditions, and the stirring speed of the precipitation reaction is 200-300 r / min.
[0014] Preferably, the detergent used for washing is an alkaline ammonium salt solution, and the pH value of the detergent used for washing is ≥10.
[0015] Preferably, the washing is performed 3 to 5 times, the washing temperature is 60 to 80° C., and the concentration of F element in the lotion after washing is ≤200 mg / L.
[0016] Preferably, the drying temperature is 120-150° C., and the insulation time is 10-12 hours.
[0017] Preferably, the calcination temperature is 950-1050° C., and the holding time is 5-10 hours.
[0018] Preferably, the calcined product is directly obtained after the calcination is completed, and the process further comprises: screening the calcined product to obtain the hollow columnar tantalum oxide; the mesh number of the sieve used for the screening is 60 meshes.
[0019] The present invention provides tantalum oxide with a hollow columnar structure prepared by the preparation method described in the above technical solution.
[0020] The present invention provides a method for preparing tantalum oxide with a hollow columnar structure, comprising the following steps: injecting a fluorotantalate solution into a precipitant for precipitation reaction to obtain a reaction liquid; the pH value of the reaction liquid is ≥9, the mass concentration of the fluorotantalate solution is ≤100 g / L in terms of Ta2O5, and the precipitant is an alkaline ammonium salt solution; solid-liquid separation of the reaction liquid to obtain a solid phase product; washing, drying and calcining the solid phase product in sequence to obtain the hollow columnar tantalum oxide. The present invention selects alkaline ammonium salt as a precipitant, and can prepare tantalum oxide with a hollow columnar structure by reasonably controlling the initial mass concentration of the fluorotantalate solution, the mixing method with the precipitant, and the pH value at the reaction end point, and the hollow columnar tantalum oxide product has good dispersibility, good fluidity, and uniform particle size distribution; at the same time, the preparation method of tantalum oxide with a hollow columnar structure provided by the present invention eliminates the use of hydrazine, reduces production costs, reduces harm to the environment and human body, and has a simple production method and a higher yield.
[0021] Furthermore, in the present invention, the precipitation reaction is carried out under stirring conditions, and the stirring speed during the precipitation reaction is 200-300 r / min. The present invention can obtain a tantalum oxide product with a more uniform hollow columnar structure by controlling the stirring speed during the reaction process.
[0022] Furthermore, in the present invention, the precipitant is an ammonium carbonate solution, and the molar concentration of the ammonium carbonate solution is 0.5 to 1.5 mol / L. The present invention can obtain a tantalum oxide product with a more uniform hollow columnar structure by selecting an ammonium carbonate solution as the precipitant and controlling the molar concentration of the ammonium carbonate solution, and can also adjust the size of the hollow structure of the hollow columnar niobium oxide product.
[0023] Furthermore, in the present invention, the injection flow rate of the fluorotantalate solution is 500 to 2000 L / h. By controlling the injection speed of the fluorotantalate solution, the present invention can obtain a tantalum oxide product with a more uniform hollow columnar structure, and at the same time regulate the size of the hollow structure of the hollow columnar niobium oxide product. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an electron microscope photograph of the hollow columnar niobium oxide product obtained after calcination in Example 1 of the present invention;
[0025] Figure 2 This is an electron microscope photograph of the hollow columnar niobium oxide product obtained after calcination in Example 2 of the present invention;
[0026] Figure 3 This is an electron microscope photograph of the hollow columnar niobium oxide product obtained after calcination in Example 3 of the present invention;
[0027] Figure 4 This is an electron microscope photograph of the niobium oxide product prepared in Comparative Example 1 of the present invention;
[0028] Figure 5 This is an electron microscope photograph of the niobium oxide product prepared in Comparative Example 2 of the present invention;
[0029] Figure 6 This is an electron microscope photograph of the niobium oxide product prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing tantalum oxide with a hollow columnar structure, comprising the following steps:
[0031] Injecting a fluorotantalate solution into a precipitant for precipitation reaction to obtain a reaction solution; the pH value of the reaction solution is ≥9, the mass concentration of the fluorotantalate solution is ≤100 g / L in terms of Ta2O5, and the precipitant is an alkaline ammonium salt solution;
[0032] Separating the reaction liquid into solid and liquid to obtain a solid phase product;
[0033] The solid phase product is washed, dried and calcined in sequence to obtain the hollow columnar tantalum oxide.
[0034] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0035] The present invention injects a fluorotantalate solution into a precipitant for precipitation reaction to obtain a reaction liquid; the pH value of the reaction liquid is ≥9, the mass concentration of the fluorotantalate solution is ≤100 g / L in terms of Ta2O5, and the precipitant is an alkaline ammonium salt solution. In the present invention, the fluorotantalate solution is an aqueous solution of fluorotantalate. The mass concentration of the fluorotantalate solution is preferably 50 to 100 g / L in terms of Ta2O5, and is specifically 100 g / L in the embodiment. The precipitant is preferably an ammonium carbonate solution, and the ammonium carbonate solution is an aqueous solution of ammonium carbonate. The molar concentration of the ammonium carbonate solution is preferably 0.5 to 1.5 mol / L, and is specifically 1.2 mol / L, 1 mol / L or 0.8 mol / L in the embodiment. The injection flow rate of the fluorotantalate solution is preferably 500 to 2000 L / h (8.3 to 33.3 L / min), more preferably 10 to 30 L / min, and is specifically 29.3 L / min in the embodiment. The precipitation reaction (including the injection process) is preferably carried out under stirring conditions, and the stirring speed of the precipitation reaction is preferably 200-300r / min, more preferably 220-300r / min, and specifically 220r / min or 280r / min in the embodiment. The precipitation reaction preferably includes the following steps: injecting the fluorotantalate solution into the precipitant, and continuing the stirring reaction after the injection is completed to obtain a reaction liquid. The injection time of the fluorotantalate solution (i.e., the precipitation reaction time) is 50-80min, and specifically 60min in the embodiment. The pH value of the reaction liquid is preferably 9. The time for continuing the stirring reaction after the injection is completed is preferably 30-40min, which can ensure that the precipitation reaction is more sufficient. The stirring reaction speed is preferably 200-300r / min, more preferably 220-300r / min, and specifically 220r / min or 280r / min in the embodiment.
[0036] After obtaining the reaction liquid, the present invention performs solid-liquid separation on the reaction liquid to obtain a solid phase product. In a specific embodiment of the present invention, the solid-liquid separation is preferably filtration. The obtained solid phase product is solid niobium hydroxide.
[0037] After obtaining the solid phase product, the present invention sequentially washes, dries and calcines the solid phase product to obtain the hollow columnar structure tantalum oxide. In the present invention, the present invention sequentially washes the solid phase product to obtain a washed solid phase product. The washing agent used for the washing is preferably an alkaline ammonium salt solution, specifically an ammonium carbonate solution, and the ammonium carbonate solution is an ammonium carbonate aqueous solution. The pH value of the washing agent used for the washing is preferably ≥10. In a specific embodiment of the present invention, the washing agent is preferably obtained by mixing and preparing an ammonium carbonate solution and hot pure water. The temperature of the washing agent is preferably 60 to 80°C. The number of washings is preferably 3 to 5 times, the washing temperature is preferably 60 to 80°C, and the concentration of the F element in the washing agent after washing is preferably ≤200 mg / L, more preferably 80 to 150 mg / L, and specifically 102 mg / L, 98 g / L or 80 g / L in the embodiment. The present invention preferably dries the washed solid phase product obtained by the washing to obtain a dried product. In the present invention, the drying temperature is preferably 120-150°C, and is specifically 120°C in the embodiment; the holding time of the drying is preferably 10-12h, and is specifically 12h in the embodiment. In a specific embodiment of the present invention, the drying is specifically preferably oven drying. The present invention preferably calcines the dried product obtained by the drying. The calcination temperature is preferably 950-1050°C, and is specifically 950°C in the embodiment. The holding time of the calcination is preferably 5-10h, and is specifically 10h in the embodiment. In the present invention, the calcined product is directly obtained after the calcination is completed. After obtaining the calcined product, the present invention preferably further includes: sieving the calcined product to obtain the hollow columnar structure tantalum oxide. The mesh number of the sieve used for the sieving is preferably 60 meshes, and the sieved material in the sieving of the present invention is the hollow columnar structure tantalum oxide.
[0038] The present invention provides tantalum oxide with a hollow columnar structure prepared by the preparation method described in the above technical solution.
[0039] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0040] Example 1
[0041] (1) Preparation: Using ammonium carbonate solution as a precipitant, put the ammonium carbonate solution into a reaction tank with a concentration of 0.8 mol / L and a fluorotantalate solution with a Ta2O5 content of 100 g / L;
[0042] (2) Reaction: adding the fluorotantalate solution to the reaction tank containing the ammonium carbonate solution at a flow rate of 29.3 L / min using a metering pump, with a stirring speed of 220 r / min, a reaction time (injection time of the fluorotantalate solution) of 60 min, a neutralization end point pH value of 9.0, and stirring continued for 30 min after neutralization; performing solid-liquid separation on the obtained solution to obtain tantalum hydroxide solid;
[0043] (3) Washing: Use ammonium carbonate solution to prepare 60-70℃ hot pure water to obtain 60-70℃ detergent. The pH of the detergent is ≥10. The amount of detergent is 5m 3 / times, the tantalum hydroxide solid after solid-liquid separation was repeatedly washed 3 times, and the fluorine content in the washing agent after the last washing was 102 mg / L;
[0044] (4) Drying: The tantalum hydroxide solid washed in step (3) is evenly spread on a stainless steel tray and placed in an electric heating box at a drying temperature of 120° C. for a holding time of 12 h;
[0045] (5) Calcination and screening: The dried tantalum hydroxide in step (4) was placed in a crucible at a standard of 1.5 kg / bowl for calcination. The calcination temperature was controlled at 950° C. and the holding time was 10 h. After cooling, the tantalum oxide solid was sieved through a 60-mesh sieve, and the sieved material was retained to obtain tantalum oxide with a hollow columnar structure.
[0046] Example 2
[0047] (1) Preparation: Using ammonium carbonate solution as a precipitant, the ammonium carbonate solution is placed in a reaction tank with a concentration of 1 mol / L, and the concentration of the fluorotantalate solution is a Ta2O5 content of 100 g / L;
[0048] (2) Reaction: using a metering pump to add the fluorotantalate solution into a reaction tank containing an ammonium carbonate solution at a rate of 29.3 L / min, the reaction time (injection time of the fluorotantalate solution) is 60 min, the stirring speed is 280 r / min, the neutralization end point pH value is 9.0, and stirring is continued for 30 min after neutralization; the obtained solution is subjected to solid-liquid separation to obtain tantalum hydroxide solid;
[0049] (3) Washing: Use ammonium carbonate solution to prepare 60-70℃ hot pure water to obtain 60-70℃ detergent. The pH of the detergent is ≥10. The amount of detergent is 3m 3 / times, the tantalum hydroxide solid after solid-liquid separation was repeatedly washed 3 times, and the fluorine content in the washing agent after the last washing was 98g / L;
[0050] (4) Drying: The tantalum hydroxide filter cake washed in step (3) is evenly spread on a stainless steel tray and placed in an electric heating box at a drying temperature of 120° C. for a holding time of 12 h;
[0051] (5) Calcination and screening: The dried tantalum hydroxide in step (4) was placed in a crucible at a standard of 1.5 kg / bowl for calcination. The calcination temperature was controlled at 950° C. and the holding time was 10 h. After cooling, the tantalum oxide solid was sieved through a 60-mesh sieve, and the sieved material was retained to obtain tantalum oxide with a hollow columnar structure.
[0052] Example 3
[0053] (1) Preparation: Using ammonium carbonate solution as a precipitant, put the ammonium carbonate solution into a reaction tank with a concentration of 1.2 mol / L, and the concentration of the fluorotantalate solution is 100 g / L of Ta2O5;
[0054] (2) Reaction: adding the fluorotantalate solution to the reaction tank containing the ammonium carbonate solution at 29.3 L / min by a metering pump, the reaction time (injection time of the fluorotantalate solution) is 60 min, the stirring speed is 280 r / min, the neutralization end point pH value = 9.0, and stirring is continued for 30 min after neutralization; the obtained solution is subjected to solid-liquid separation to obtain tantalum hydroxide solid;
[0055] (3) Washing: Use ammonium carbonate solution to prepare 60-70℃ hot pure water to obtain 60-70℃ detergent. The pH of the detergent is ≥10. The amount of detergent is 5m 3 / times, the tantalum hydroxide solid after solid-liquid separation is repeatedly washed 3 times, and the fluorine content in the washing agent after the last washing is 80g / L;
[0056] (4) Drying: The tantalum hydroxide solid washed in step (3) is evenly spread on a stainless steel tray and placed in an electric heating box at a drying temperature of 120° C. for a holding time of 12 h;
[0057] (5) Calcination and screening: The dried tantalum hydroxide in step (4) was placed in a crucible at a standard of 1.5 kg / bowl for calcination. The calcination temperature was controlled at 950° C. and the holding time was 10 h. After cooling, the tantalum oxide solid was sieved through a 60-mesh sieve, and the sieved material was retained to obtain tantalum oxide with a hollow columnar structure.
[0058] The scanning electron microscopy images of the tantalum oxide prepared in Examples 1 to 3 are as follows: Figure 1 , Figure 2 and Figure 3 As shown, from Figures 1 to 3 It can be seen that at different precipitant concentrations and different stirring speeds, tantalum oxide is an agglomerate of a hollow columnar structure, and the particle size distribution (hollow columnar structure) of Example 3 is relatively uniform.
[0059] Comparative Example 1
[0060] (1) Preparation: Use carbonamide solution as a precipitant, put the carbonamide solution into a reaction tank, the concentration of which is 1.2 mol / L, and the concentration of fluorotantalate solution is 100 g / L of Ta2O5;
[0061] (2) Reaction: using a metering pump to add the fluorotantalate solution to a reaction tank containing the carbonamide solution at a rate of 29.3 L / min, the reaction time (injection time of the fluorotantalate solution) is 60 min, the stirring speed is 280 r / min, the neutralization end point pH value = 9.0, and stirring is continued for 30 min after neutralization; the obtained solution is subjected to solid-liquid separation to obtain tantalum hydroxide solid;
[0062] (3) Washing: Use carbonamide solution to prepare 60-70℃ hot pure water to obtain 60-70℃ detergent. The pH of the detergent is ≥10. The amount of detergent is 5m 3 / times, the tantalum hydroxide solid after solid-liquid separation is repeatedly washed 3 times, and the fluorine content in the washing agent after the last washing is 80g / L;
[0063] (4) Drying: The tantalum hydroxide solid washed in step (3) is evenly spread on a stainless steel tray and placed in an electric heating box at a drying temperature of 120° C. for a holding time of 12 h;
[0064] (5) Calcination and screening: The dried tantalum hydroxide obtained in step (4) is placed in a crucible at a standard of 1.5 kg / bowl for calcination. The calcination temperature is controlled at 950° C. and the holding time is 10 h. After cooling, the tantalum oxide solid is sieved through a 60-mesh sieve, and the sieved material is retained to obtain tantalum oxide.
[0065] Figure 4 This is an electron microscope photograph of the tantalum oxide product obtained by using carbonamide solution as a precipitant in Comparative Example 1. Figure 4 It can be seen that after changing the type of precipitant in Comparative Example 1, tantalum oxide with a hollow structure cannot be obtained.
[0066] Comparative Example 2
[0067] (1) Preparation: Using ammonium carbonate solution as a precipitant, put the ammonium carbonate solution into a reaction tank with a concentration of 1.2 mol / L, and the concentration of the fluorotantalate solution is 100 g / L of Ta2O5;
[0068] (2) Reaction: adding the fluorotantalate solution to the reaction tank containing the ammonium carbonate solution at 29.3 L / min by a metering pump, the reaction time (injection time of the fluorotantalate solution) is 60 min, the stirring speed is 280 r / min, the neutralization end point pH value = 8.0, and stirring is continued for 30 min after neutralization; the obtained solution is subjected to solid-liquid separation to obtain tantalum hydroxide solid;
[0069] (3) Washing: Use ammonium carbonate solution to prepare 60-70℃ hot pure water to obtain 60-70℃ detergent. The pH of the detergent is ≥10. The amount of detergent is 5m 3 / times, the tantalum hydroxide solid after solid-liquid separation is repeatedly washed 3 times, and the fluorine content in the washing agent after the last washing is 80g / L;
[0070] (4) Drying: The tantalum hydroxide solid washed in step (3) is evenly spread on a stainless steel tray and placed in an electric heating box at a drying temperature of 120° C. for a holding time of 12 h;
[0071] (5) Calcination and screening: The dried tantalum hydroxide obtained in step (4) is placed in a crucible at a standard of 1.5 kg / bowl for calcination. The calcination temperature is controlled at 950° C. and the holding time is 10 h. After cooling, the tantalum oxide solid is sieved through a 60-mesh sieve, and the sieved material is retained to obtain tantalum oxide.
[0072] Figure 5 This is an electron microscope photo of the tantalum oxide product obtained in Comparative Example 2. Figure 5 It can be seen that in Comparative Example 2, by changing the pH value at the reaction end point of the precipitation reaction, tantalum oxide with a hollow columnar structure cannot be obtained.
[0073] Comparative Example 3
[0074] (1) Preparation: Using ammonium carbonate solution as a precipitant, put the ammonium carbonate solution into a reaction tank with a concentration of 1.2 mol / L, and the concentration of the fluorotantalate solution is 100 g / L of Ta2O5;
[0075] (2) Reaction: using a metering pump to add the ammonium carbonate solution to a reaction tank containing the fluorotantalate solution at a rate of 17.6 L / min, the reaction time (injection time of the ammonium carbonate solution) is 60 min, the stirring speed is 280 r / min, the neutralization end point pH value is 9.0, and stirring is continued for 30 min after neutralization; the obtained solution is subjected to solid-liquid separation to obtain tantalum hydroxide solid;
[0076] (3) Washing: Use ammonium carbonate solution to prepare 60-70℃ hot pure water to obtain 60-70℃ detergent. The pH of the detergent is ≥10. The amount of detergent is 5m 3 / times, the tantalum hydroxide solid after solid-liquid separation is repeatedly washed 3 times, and the fluorine content in the washing agent after the last washing is 80g / L;
[0077] (4) Drying: The tantalum hydroxide solid washed in step (3) is evenly spread on a stainless steel tray and placed in an electric heating box at a drying temperature of 120° C. for a holding time of 12 h;
[0078] (5) Calcination and screening: The dried tantalum hydroxide obtained in step (4) is placed in a crucible at a standard of 1.5 kg / bowl for calcination. The calcination temperature is controlled at 950° C. and the holding time is 10 h. After cooling, the tantalum oxide solid is sieved through a 60-mesh sieve, and the sieved material is retained to obtain tantalum oxide.
[0079] Figure 6This is an electron microscope photo of the tantalum oxide product obtained in Comparative Example 3. Figure 6 It can be seen that in Comparative Example 3, adding the ammonium carbonate solution into the fluorotantalate solution cannot obtain tantalum oxide with a hollow columnar structure.
[0080] The tantalum oxide products prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are used as raw materials for metallurgical grade tantalum powder. The direct yield and comprehensive yield of metallurgical grade tantalum powder prepared by the hollow columnar tantalum oxide prepared in Examples 1 to 3 are higher than those of the tantalum oxide products prepared in Comparative Examples 1 to 3. The specific data are shown in Table 1.
[0081] Table 1 Yield of metallurgical grade tantalum powder prepared from tantalum oxide prepared in Examples 1 to 3 and Comparative Examples 1 to 3
[0082] NO. Morphology and structure Direct yield / % Comprehensive yield / % Example 1 Hollow column 88.23 94.58 Example 2 Hollow column 87.91 93.92 Example 3 Hollow column 89.65 95.24 Comparative Example 1 Solid rod 86.74 92.36 Comparative Example 2 Irregular particles 85.87 91.54 Comparative Example 3 Regular granular 86.18 91.85
[0083] In Table 1: Direct yield rate = weight of directly obtained product / weight of product obtained by input amount;
[0084] Comprehensive recovery rate = (weight of directly recovered products + weight of recoverable products in the process) / weight of products obtained based on the amount of material added.
[0085] From the above examples, it can be seen that the present invention selects alkaline ammonium salt as a precipitant, and by reasonably controlling the initial mass concentration of the fluorotantalate solution, the mixing method with the precipitant, and the pH value at the reaction end point, a hollow columnar structure tantalum oxide can be prepared, and the hollow columnar structure tantalum oxide product has good dispersibility, good fluidity, and uniform particle size distribution; at the same time, the preparation method of the hollow columnar structure tantalum oxide provided by the present invention eliminates the use of hydrazine, reduces production costs, reduces harm to the environment and human body, and has a simple production method and a higher yield. Furthermore, the present invention can obtain a hollow columnar structure tantalum oxide product with a more uniform morphology by controlling the stirring speed of the reaction process and controlling the molar concentration of the ammonium carbonate solution.
[0086] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing tantalum oxide with a hollow columnar structure, characterized in that: The following steps are involved: Injecting the fluorotantalate solution into a precipitant for precipitation reaction to obtain a reaction liquid; the pH value of the reaction liquid is ≥9, the mass concentration of the fluorotantalate solution is ≤100 g / L in terms of Ta2O5, and the precipitant is an alkaline ammonium salt solution; Separating the reaction liquid into solid and liquid to obtain a solid phase product; The solid phase product is washed, dried and calcined in sequence to obtain the hollow columnar tantalum oxide.
2. The preparation method according to claim 1, characterized in that: The mass concentration of the fluorotantalate solution is 50 to 100 g / L in terms of Ta2O5; the injection flow rate of the fluorotantalate solution is 500 to 2000 L / h.
3. The preparation method according to claim 1, characterized in that: The precipitant is an ammonium carbonate solution, and the molar concentration of the ammonium carbonate solution is 0.5-1.5 mol / L.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The precipitation reaction is carried out under stirring conditions, and the stirring speed during the precipitation reaction is 200-300 r / min.
5. The preparation method according to claim 1, characterized in that: The washing agent used in the washing is an alkaline ammonium salt solution, and the pH value of the washing agent used in the washing is ≥10.
6. The preparation method according to claim 1 or 5, characterized in that: The washing is performed 3 to 5 times, the washing temperature is 60 to 80° C., and the concentration of F element in the washing agent after washing is ≤200 mg / L.
7. The preparation method according to claim 1, characterized in that: The drying temperature is 120-150° C., and the heat preservation time is 10-12 hours.
8. The preparation method according to claim 1, characterized in that: The calcination temperature is 950-1050° C., and the heat preservation time is 5-10 hours.
9. The preparation method according to claim 1, characterized in that: The calcined product is directly obtained after the calcination is completed, and the method further includes: screening the calcined product to obtain the hollow columnar tantalum oxide; the mesh number of the sieve used for the screening is 60 meshes.
10. Tantalum oxide with a hollow columnar structure prepared by the preparation method according to any one of claims 1 to 9.